2018
DOI: 10.37275/ijr.v8i1.11
|View full text |Cite
|
Sign up to set email alerts
|

Myelopathy caused by Ossification of Thoracic Ligamentum Flavum

Abstract: Hypertrophy of the posterior spinal elements leading to compromise of the spinal canal and its neural elements is a well-recognized pathological entity affecting the lumbar or cervical spine. Such stenosis of the thoracic spine in the absence of a generalized rheumatological,metabolic, or orthopedic disorder, or a history of trauma is generally considered to be rare. Spinal ligaments, such as the ligamentum flavum (LF), are prone to degeneration and can lead to back pain and nerve dysfunction. Ossification of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
2
0

Year Published

2020
2020
2020
2020

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 13 publications
0
2
0
Order By: Relevance
“…The study reported a case of OLF at the level of T9-11. 12 Our case-report is the first publication on multilevel OLF from Indonesia.…”
Section: Discussionmentioning
confidence: 83%
See 1 more Smart Citation
“…The study reported a case of OLF at the level of T9-11. 12 Our case-report is the first publication on multilevel OLF from Indonesia.…”
Section: Discussionmentioning
confidence: 83%
“…3 There was only one Indonesian OLF case that had been published. 12 To the best of our knowledge, this is the first published multilevel OLF case from Indonesia. Through this case report we aim to describe the natural history of the patient and our treatment strategy in managing multilevel OLF case.…”
mentioning
confidence: 84%